Entropy-Enthalpy Compensation and its Significance - in Particular for Nanoscale Events - Starikov, E.B. (Journal of Applied Solution Chemistry and Modeling, 2013)
The basic thermodynamics behind the well-known, up to now hotly debated, notion of entropy-enthalpy compensation (EEC) is analyzed here in detail. Namely, any valid EEC phenomenon is considered using Carnot-cycle-type model, in which micro-phase transitions (MPTs) play a crucial role. Such MPTs could typically be some cooperative processes in (supra)molecular aggregates. Thus, the MPT notion ought to help rationalize the occurrence of the EEC in connection with some pertinent microscopic mechanisms.